Cyanobacterial diversity of Petuniabukta, Billefjorden, central Spitsbergen - Komárek, J. (Jiří); Kováčik, L.; Elster, J. (Josef); Komárek, O. (Ondřej) (Polish Polar Research, 2012)
The diversity of cyanobacterial assemblages from various microhabitats in the Arctic area of Petuniabukta, Billefjorden, central Svalbard, was described. The present article contains the introductory common review of the cyanobacterial diversity and ecological data concerning main habitats, while the characteristics of individual taxonomic groups will be presented in following specific studies. Eight distinct main habitats were recognized, which differed in their species composition and especially the dominant species. More than 80 morphospecies were registered during our investigation, but only about 1/3 of them could be assigned to known and described taxa. The diversity of unicellular and colonial morphotypes (36 taxa) was higher than other groups.